2015
DOI: 10.1016/j.ridd.2014.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Screening for intellectual disability in persons with a substance abuse problem: Exploring the validity of the Hayes Ability Screening Index in a Dutch-speaking sample

Abstract: There is an increasing interest in screening instruments to detect Intellectual Disability (ID) in a quick and accurate way in mental health services as well as in the criminal justice system in order to provide appropriate support for people with undetected needs caused by ID. An instrument that has been proven to be useful in both settings is the Hayes Ability Screening Index (HASI). This study assessed the validity of the Dutch version of the HASI in persons with a substance abuse problem residing in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
(51 reference statements)
2
23
0
1
Order By: Relevance
“…The results in Paper III, found the HASI to be a good screening instrument for detecting possible ID/BID in the SUD population. Similar results have been reported by To et al (2015). The HASI can be easily administered by SUD personnel to all patients and form the basis for further assessment and adjusted treatment.…”
Section: Identification and Diagnosticssupporting
confidence: 81%
See 1 more Smart Citation
“…The results in Paper III, found the HASI to be a good screening instrument for detecting possible ID/BID in the SUD population. Similar results have been reported by To et al (2015). The HASI can be easily administered by SUD personnel to all patients and form the basis for further assessment and adjusted treatment.…”
Section: Identification and Diagnosticssupporting
confidence: 81%
“…The Norwegian version was validated against standardized IQ tests and is recommended for ID screening among both prisoners and psychiatric patients in Norway (Søndenaa, Bjørgen, & Nøttestad, 2007;Søndenaa et al, 2008;Søndenaa et al, 2011). A study of patients with SUD also found the HASI to have good convergent and discriminative validity for this population when IQ was used as the validation criterion (To, Vanheule, Vanderplasschen, Audenaert, & Vandevelde, 2015), but the authors encourage further study of the validity of HASI for predicting ID in SUD based on all three ICD-10/DSM-5 criteria.…”
Section: Screening For Id In Individuals With Sudmentioning
confidence: 99%
“…Although possibly over‐inclusive of borderline intellectual disability (Cashin et al ), the HASI appears to have good predictive utility in identifying individuals with borderline intellectual functioning who are likely to encounter problems navigating, accessing and managing their own healthcare requirements. Furthermore, the HASI cut‐off has been recently validated for use in populations with comorbid psychiatric and SUDs (To et al ). Our comparison of the total HASI scores between the intellectual disability prior‐identified/not‐identified subgroups demonstrated that the prior identification of intellectual disability was not an indication of impairment severity.…”
Section: Discussionmentioning
confidence: 99%
“…20 It was developed specifically to detect MID/BIF (IQ 50-85) in people in a range of settings, such as healthcare or social service settings, police stations and shelters for the homeless. The SCIL adds to other screeners for intellectual disability, such as the Hayes Ability Screening Index, 22 because it screens for BIF in addition to MID. The SCIL was validated in an adult sample by comparing the scores obtained with test results from the WAIS III.…”
Section: Mid/bif Screening With the Scilmentioning
confidence: 99%